Betting for the poor: Exploring gambling as a financial strategy for low income households in Colombia. - Molano, Juan Sebastian (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Every day, low-income households make financial decisions about how to allocate their money. This is especially challenging for them as they face high limitations in their financial resources and sources of income. Gambling is one of such available options. However, it has been deeply studied as compulsive behavior or pathology, but it has been systematically ignored as a gateway to understand individualâÃÃ´s motivations to allocate finite, limited, scarce resources in games of chance as a financial strategy. In order to explore the role of gambling as a financial strategy, the case of the Colombian gambling game called chance is used. Chance is widely played in Colombia, mainly by low-income households. In contrast to other financial decisions, playing chance is highly motivated by cultural and social factors related with luck, superstition, regret aversion and subjective probability which play a fundamental role in the decision making process. In addition to this, the exclusion of these households from the formal financial system restricts their ability to access different management financial tools that could allow them to achieve better standards of living. Finally, key learning findings from the Colombian case are identified to illustrate the relevance and need to understand the role of gambling in the life of low-income households.